Study on the effect of Hanging ratio in gill nets - Duman, E.; Pala, M.; Yuksel, F. (Indian Veterinary Journal, 2006)
Gill net is one of the most important passive fishing gear used in freshwater and coastal waters. Usually it consists of a single wall made of polyamide monofilament (Fabi et al., 2002). The amount of fish cought with gill nets changes with the mesh size, mesh shape, twine thickness of material, colour and hanging ratio (Hay et al., 1986; Holst et al., 2002). The prominent advantage of gill nets is their selectivity of catching uniform sized fish. The hanging ratios of gill nets almost determined the size of catch though the other properties such as colour, depth etc. must be considered. In this study, the effect of selectivity of different hanging ratios at multifilament gill nets was investigated in Keban Dam Lake (Elazig-Turkey) where gill nets with a hanging ratios of 0.50 is widely in use.
Keywords: Selectivity